2013
DOI: 10.1371/journal.pone.0064831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucocorticoid Receptor Density on Ligand-Independent Dimerization, Cooperative Ligand-Binding and Basal Priming of Transactivation: A Cell Culture Model

Abstract: Glucocorticoid receptor (GR) levels vary between tissues and individuals and are altered by physiological and pharmacological effectors. However, the effects and implications of differences in GR concentration have not been fully elucidated. Using three statistically different GR concentrations in transiently transfected COS-1 cells, we demonstrate, using co-immunoprecipitation (CoIP) and fluorescent resonance energy transfer (FRET), that high levels of wild type GR (wtGR), but not of dimerization deficient GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 108 publications
(147 reference statements)
6
47
1
Order By: Relevance
“…The maximum amount of endogenous GR in COS-1 is 61 nM based on the previously reported 111 000 molecules per cell (1420 fmol/mg) [17] and our finding of a 3 pL cell volume. Moreover, 16 200 fmol/mg in cytotrophoblasts [18] was calculated to be 701 nM using the same method.…”
Section: Determination Of Dissociation Constant Of Egfp-gr In Homodimsupporting
confidence: 65%
See 1 more Smart Citation
“…The maximum amount of endogenous GR in COS-1 is 61 nM based on the previously reported 111 000 molecules per cell (1420 fmol/mg) [17] and our finding of a 3 pL cell volume. Moreover, 16 200 fmol/mg in cytotrophoblasts [18] was calculated to be 701 nM using the same method.…”
Section: Determination Of Dissociation Constant Of Egfp-gr In Homodimsupporting
confidence: 65%
“…(13)(14)(15), the fractions of monomeric and homodimeric EGFP-GR (F m and F d ) are shown as Eqs. (16) and (17).…”
Section: Determination Of Dissociation Constant Of Egfp-gr In Homodimmentioning
confidence: 99%
“…Considering that P 4 and MPA have previously been shown to have different binding affinities and transcriptional activities via the GR (11,92), it was surprising that these progestogens displayed similar GR-mediated effects in the Ect1/E6E7 cell line. However, the relative affinities of P 4 and MPA for the GR may be different in this cell line compared with other cell lines, as it has previously been shown that the concentration of GR determines the binding affinity of a ligand for the receptor (93). Moreover, as we have previously shown that P 4 and MPA differentially regulate cytokine gene expression in a cell-and promoter-specific manner (39), discrepancies between the results from this study and others using synthetic GRE-containing promoters in COS-1 cells, for example (11), may be due to either cell-or promoter-specific effects.…”
Section: Discussionmentioning
confidence: 79%
“…The course of DNAprotein assembly has been discussed for a number of transcription factors, and the consensus is that there are three possible mechanisms. One mechanism implies that receptor dimerization could take place in the cytoplasm before its nuclear translocation [100,101]. The dimer pathway model sustains that transcription factors must dimerize on the nuclear environment to permit DNA binding, and the monomer pathway postulates that two monomers can bind sequentially to promoter sequences and protein assembly takes place during the in situ dimerization [102,103].…”
Section: Nuclear Eventsmentioning
confidence: 99%
“…The dimer pathway model sustains that transcription factors must dimerize on the nuclear environment to permit DNA binding, and the monomer pathway postulates that two monomers can bind sequentially to promoter sequences and protein assembly takes place during the in situ dimerization [102,103]. Also, it has been suggested that the level of receptor expression affects the formation of homodimers [101]. Nevertheless, it is still unknown whether steroid receptor homodimers form before or as a result of binding to hormone-responsive elements because some studies have showed some evidence favoring the monomer pathway model [104,105], whereas others support the dimer pathway model [106][107][108].…”
Section: Nuclear Eventsmentioning
confidence: 99%